Chapter 8: Patient Education and Counselling (Foundations in Clinical Pharmacy Practice, 2025)
AuthorDr. Farheen Malik, Assistant Professor, Department of Pharmacy Practice, Sir C.R. Reddy College of Pharmaceutical Sciences, Eluru, Andhra Pradesh, IndiaAbstractPatient education and counseling skills fundamentally transform medication knowledge into improved health behaviors through effective communication strategies addressing diverse patient needs. Counseling techniques employ patient-centered approaches including show-and-tell demonstrations, teach-back verification, and prioritized information delivery focused on essential action-oriented content rather than exhaustive details. Health literacy assessment guides communication complexity through recognition of literacy barriers, numeracy challenges, and comprehension limitations requiring plain language, visual aids, and simplified instructions appropriate for diverse populations. Medication adherence enhancement addresses intentional and unintentional non-adherence through multifaceted interventions including regimen simplification, reminder systems, side effect management, and affordability solutions tailored to specific barriers. Educational materials development incorporates design principles including appropriate reading level, visual reinforcement, cultural relevance, and practical organization enhancing comprehension and retention. Motivational interviewing techniques facilitate behavior change through collaborative exploration of ambivalence, resistance reduction, and intrinsic motivation enhancement rather than confrontational approaches or simple information provision. These integrated skills enable pharmacists to effectively communicate medication information while addressing psychological, social, and practical barriers to optimal medication use.Keywords: Patient-Centered Communication, Adherence Support, Health Behavior Change, Therapeutic Alliance, Medication LiteracyVIEW PDF